Comparison Study of the Actual Method and the Economic Order Quantity (EOQ) Method in Controlling Food Raw Materials Inventories at Royal Tulip Gunung Geulis Resort & Golf - Sekti Rahardjo; Aditya Sugih Setiawan; M. Ridwan Permana; Syaiful Anwar (East Asian Journal of Multidisciplinary Research, 2023)
The aim of this study is to determine the effect of the Economic Order Quantity (EOQ) method in inventory control, in terms of inventory profitability and non-financial performance (production efficiency, timely delivery, product quality). The research is descriptive with a quantitative approach. This study calculates the optimal inventory raw materials of chicken, beef, and lamb. The EOQ is more optimal and efficient, showed by the ordering cost difference is Rp 702,000,-, the total storage cost difference is Rp 2,863,917, -, the difference between the total purchase cost is Rp 57,278,334, -, and the difference in the total cost of inventory is Rp. 3,565,917,-. By using the EOQ method, Royal Tulip can save a total cost of Rp 64,410,168,-.